PENENTUAN LOKASI DERMAGA FERI PENYEBERANGAN DI NIPAH KUNING, JERUJU DAN SUNGAI RENGAS - Hardiyanto, Satya; ., Akhmadali; Azwansyah, Heri (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2014)
West borneo province is one of place have rivers, so transportation of water very needed. For support transportation of water then the place must have a dock. One of part from port is a dock. This research purpose is determine a dock location from third alternative location that have in. In theÂ research, to get a location from third location that with use AHP methods (Analitycal Hierarchy Process). First step of methods is determine criteria that used as comparison, the make hierarchy structures from the first step. Then, the data be treated with use couple matriks. From the result derive weight value from the third location. The highest of weight value from the third location is Nipah Kuning, so Nipah Kuning is a location that will build a cross dock. The conclusion, AHP methods (Analitycal Hierarchy Process) is fit to use to determine a decision that have two or comparison value. Â Keywords: dock, Analitycal Hierarchy Process, matrix of comparsion